2021
DOI: 10.1080/13814788.2021.1962845
|View full text |Cite
|
Sign up to set email alerts
|

SERIES: eHealth in primary care. Part 5: A critical appraisal of five widely used eHealth applications for primary care – opportunities and challenges

Abstract: Background Given the pressure on modern healthcare systems, eHealth can offer valuable opportunities. However, understanding the potential and challenges of eHealth in daily practice can be challenging for many general practitioners (GPs) and their staff. Objectives To critically appraise five widely used eHealth applications, in relation to safe, evidence-based and high-quality eHealth. Using these applications as examples, we aim to increase understanding of eHealth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
(71 reference statements)
0
11
0
4
Order By: Relevance
“…Third, our intervention content was integrated into app-based interventions that are used in a blended care setting in primary and secondary care. There is a growing body of literature that recognizes that blended interventions are more likely to be used and effective than stand-alone interventions [ 36 , 75 - 77 , 79 - 81 ]. By combining aforementioned elements, we expect that our intervention could positively contribute to sustainable health behavior change, although this still needs to be researched.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our intervention content was integrated into app-based interventions that are used in a blended care setting in primary and secondary care. There is a growing body of literature that recognizes that blended interventions are more likely to be used and effective than stand-alone interventions [ 36 , 75 - 77 , 79 - 81 ]. By combining aforementioned elements, we expect that our intervention could positively contribute to sustainable health behavior change, although this still needs to be researched.…”
Section: Discussionmentioning
confidence: 99%
“…Another strength is that Homelab was developed in cocreation with GPs. Cocreation in eHealth interventions is an important precondition for good adoption of eHealth [11]. Homelab was piloted and developed for general practices in the Netherlands.…”
Section: Limitations and Strengths Of This Studymentioning
confidence: 99%
“…Homelab was piloted and developed for general practices in the Netherlands. However, a service like Homelab can also be implemented in other European countries with comparable primary health care systems where the GP is the first gatekeeper-in particular, Nordic countries are relatively advanced in adopting eHealth [11].…”
Section: Limitations and Strengths Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has showed that most patients (more than 76%) use checkers solely for self-diagnosis [39]. As such, if checkers are not meticulously engineered and rigorously evaluated on their diagnostic capabilities, they may put patients at risk [4, 21, 33]. To this end, this paper focuses on verifying the diagnostic accuracy of checkers due to serving as the underpinning of any aspired benefit.…”
Section: Introductionmentioning
confidence: 99%